2009
DOI: 10.1007/978-3-540-93864-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Intermolecular Interactions in T Cells

Abstract: The use of appropriate fluorescent proteins has allowed the use of FRET microscopy for investigation of intermolecular interactions in living cells. This method has the advantage of both being dynamic and of working at the subcellular level, so that the time and place where proteins interact can be visualized. We have used FRET microscopy to analyze the interactions between the T cell antigen receptor and the coreceptors CD4 and CD8. This chapter reviews data on how these coreceptors are recruited to the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Instead, Forster resonance energy transfer (FRET) can be employed to study colocalization on the scale of a few nanometers and therefore provides information about molecular interactions (Gascoigne et al 2009). Using this technique, FRET was detected between PLC-g1 and either LAT, c-Cbl, Vav or SLP-76, as well as and Nck within microclusters, suggesting direct interactions of these proteins within microclusters Braiman et al 2006).…”
Section: Lat Microclusters: Sites Of Nucleation Of Signaling Complexesmentioning
confidence: 99%
“…Instead, Forster resonance energy transfer (FRET) can be employed to study colocalization on the scale of a few nanometers and therefore provides information about molecular interactions (Gascoigne et al 2009). Using this technique, FRET was detected between PLC-g1 and either LAT, c-Cbl, Vav or SLP-76, as well as and Nck within microclusters, suggesting direct interactions of these proteins within microclusters Braiman et al 2006).…”
Section: Lat Microclusters: Sites Of Nucleation Of Signaling Complexesmentioning
confidence: 99%
“…The FRET data, in combination with striking nuclear magnetic resonance measurements, led to the conclusion that CD3ε binds to the inner leaflet of the plasma membrane, burying tyrosine residues that are crucial for activation in the lipid bilayer. FRET has also been used to look at interactions between the TCR and co-receptors 94 .…”
Section: Molecular Interactions and Dynamicsmentioning
confidence: 99%
“…These two methods are widely used in the study of protein-protein interactions in vivo, and can directly visualize protein interactions in living cells (58)(59)(60)(61). Based on these assays, we have found that Itk forms head-to-tail dimers only in the plasma membrane, but not in the cytoplasm, suggesting that Itk does not form dimers in the inactive state (57).…”
Section: Conformation Of Activated Itkmentioning
confidence: 90%